Seasonal Dynamics of Bacterial Indicators in the Albanian Part of Prespa Lake - Hamzaraj, E.; Lazo, P.; Koja, O.; Paparisto, A.; Laknori, O.; Duka, S. (Asian Journal of Chemistry, 2012)
The aim of present study is to assess the water quality of Prespa Lake according to microbiological indicators, such as total coliform bacteria and heterotrophic bacteria. Prespa Lake is part of Prespa National Park which is one of the protected areas in Albania and, apart from this, is an international focal point mentioned for its high biodiversity. MPN index was used for evaluation of total coliform bacteria in water. The number of heterotrophic bacteria was determined by counting colonies on plates with plate count agar. Samples were collected from May 2008 to May 2009 in two stations. The highest value of total coliform bacteria in water is registered in May, while the number of heterotrophic bacteria has not changed too much during the year. According to the received results for heterotrophic bacteria, the Lake Prespa water quality was in the frames of I-II class.